Evaluation The Prevalence and Impact of Helicobacter pylori Infection among Patients with Hepatitis C Virus - Kazaal, Meraim (Journal of Biomedicine and Biochemistry, 2024)
Background Recently, we have noticed an increase in stomach disor- ders in people infected with hepatitis C virus (HCV) for this reason we studied the prevalence and effect of Helicobacter pylori (H. pylori) infec- tion in HCV patients in Iraq. Method: Our study included 100 cases of HCV and 100 healthy control group. The necessary clinical and labora- tory tests were performed to diagnose HCV and H. pylori. Liver enzymes, creatinine bilirubin, IL-6, 8, 17, TNF-α were evaluated according to Kits protocol.Results H. pylori isolated from most HCV patients (61%) while the infection appeared in a lower percentage (31%) among control. Results showed that the most common HCV genotype is genotype 4 with a rate of 43%, followed by 1 and 6 with a rate of 25% and 17%, respectively. In HCV cases, females were most infected with H. pylori at a rate of (75%) compared to males (25%). Confection of HCV and H. pylori had a higher Meld Score than their non-infected peers (p = 0.0078) and Chronic active hepatitis and Child-Pugh score A, B, and C increased by 42%, 43%, 76%, and 78%, respectively, among patients with confection, and these percent- ages were different from their peers with HCV infection only. Elevated AST and ALT in confection (61.4 and 79.7U/L respectively) compared to HCV patients uninfected by H. pylori (22.7 and 47.1 U/L respectively). Moreover, an increase in the concentration of IL-17, TNF-α, and IL-6 in confection (131pg/ml, 99.2 ng/ml, and 79.4 ng/ml, respectively) com- pared with H.pylori uninfected HCV patients (59.4 pg/ml, 75.6 ng/ml and 58.3ng/ml, respectively).Conclusion increasing prevalence of H. pylori in patients with HCV led to liver ulcers, imbalances in liver enzymes, in addition to immune disorders. A destructive treatment for H. pylori may be beneficial for those patients who suffer from chronic HCV.